Radioactivity in the environment - Valkovic, Vlado (New York : Elsevier Science B.V., 2000)
Numerous sources of ionizing radiation can lead to human exposure: natural sources, nuclear explosions, nuclear power generation, use of radiation in medical, industrial and research purposes, and radiation emitting consumer products. Before assessing the radiation dose to a population one requires a precise knowledge of the activity of a number of radionuclides. The basis for the assessment of the dose to a population from a release of radioactivity to the environment, the estimation of the potential clinical heath effects due to the dose received and, ultimately, the implementation of countermeasures to protect the population, is the measurement of radioactive contamination in the environment after the release. It is the purpose of this book to present the facts about the presence of radionuclides in the environment, natural and man made. There is no aspect of radioactivity, which has marked the passing century, not mentioned or discussed in this book.
Chapter headings: Introduction, Radioactive Nuclides in Nature. Technologically Modified Exposure to Natural Radiation. Man Made Radioactivity. Measurements of Radioactivity. Radiation Safety. Nuclear Fuel Cycle for Electricity Generation. The Bomb. Monitoring Accidentally Released Radionuclides in the Environment. The Bomb Test Sites. International Safeguards. Comprehensive Test Ban Treaty.
Ηλεκτρονικό βιβλίο
Keywords: Radioecology; Radioactive pollution; Radioactivity -- Measurement; Electronic books